MANAGEMENT STUDENTS’ NEED ANALYSIS FOR ENGLISH FOR SPECIFIC PURPOSES’ (ESP) TEACHING DESIGN - Haya Haratikka; Anita Purba (CV. RADJA PUBLIKA, 2024)
Teaching design that always upgrading are believe will improve learners’ achievements. The importance of English mastery for management study program will support their education and also carreer. The students ability in English mastery should be improved through many activities during their study. Therefore, lectures should analyze their needs based on ESP before conducting teaching and learning process to meet their future career, as a business manager. Having a good communication and ability to solve a problem become their main demands. Speaking is one of the most essential skill which learners should master well to bridge them all. However, their speaking skill is still lack. They need exposure to improve it. Thus, from the data, mostly informants want to have more semesters to practice English. This research was a qualitative descriptive. The data were obtainned from the first year of 144 management students through interviews, close-ended questionaire, and observation. As the findings, emphasizing speaking abilities is the best way for management students to improve their English. It ought to be used in dynamic, students-center classroom while the lecturers play the role as facilitator. These components seek to raise students’ sense of self-worth and get them ready for the workforce.